(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper’s goal is to investigate the Eyring-Powell nano liquid past rotating disk. Thermal radiation and chemical reaction have been used to study heat and mass transmission. Convective characteristics, as well as heat and mass conditions, are studied. Through appropriate transformations, highly non-linear partial differential equation systems are transformed into nonlinear ordinary differential equations. Implementing bvp4c uses the transmuted ordinary differential equations. Through graphical representation, the effects of promising physical characteristics have been investigated.